Development of Banan Application Assisted the Learning Cycle 5e to Enhance Conceptual Understanding Ability - Ofi Laili Nur Shochifah; Megita Dwi Pamungkas; Paskalia Pradanti (Universitas Pendidikan Mandalika, 2025)
The advancement of technology today poses a unique challenge in the field of education, particularly requiring educators to innovate effectively. The learning media currently used are less engaging and interactive. This research was conducted to assess the effectiveness of an interactive learning media in the form of the Banan application. This study is motivated by students' low learning motivation and their poor ability to understand mathematical concepts. The teaching methods often rely on lectures, which result in students being less active during learning. The purpose of this study is to describe the feasibility and effectiveness of the Banan application assisted by the Learning Cycle 5E model. This research is a development research and development (R&D) study, namely ADDIE, which has 5 stages: Analysis, Design, Development, Implementation, and Evaluate. The method of data collection in this study involved observations, interviews, expert validation tests for media and material, questionnaires, as well as pretests and posttests instruments. The results of the media expert validation test obtained a score of 89% with a very feasible category, while the material expert validation test obtained a score of 82% with a very feasible category. Meanwhile, the effectiveness test results of the pretest and posttest showed an average Gain Score of 0.59 with moderate criteria. Student responses scored 84.17% with a very good category, while teacher responses had an average score of 83.20% with a very good category. These results conclude that the Banan application assisted by the 5E learning Cycle model is deemed feasible for use in learning.